Looking Into the Future: The Current and Future State of IR in Canada. Issue 1 (February 2023) - Graham, Tara; Hamidizadeh, Ramin; Wright, Chris; Wong, Jason K.; Brown, Andrew; Menard, Alexandre; Mujoomdar, Amol
This review explores the priorities and future opportunities of interventional radiology in Canada.